2022
DOI: 10.3390/challe13020028
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hopeful Resilience Regarding Depression and Anxiety with a Narrative Method of Ordering Memory Effective in Researchers Experiencing Burnout

Abstract: Depression and anxiety are prevalent, persistent, and difficult to treat industrialized world mental health problems that negatively modify an individual’s life perspective through brain function imbalances—notably, in the amygdala and hippocampus. Primarily treated with pharmaceuticals and psychotherapy, the number of individuals affected plus the intensity of their suffering continues to rise post-COVID-19. Decreasing depression and anxiety is a major societal objective. An approach is investigated that cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 73 publications
0
21
0
1
Order By: Relevance
“…This may reflect the evidence that resilience moderates the relationship between severity of depressive episodes in bipolar disorder and subjective well-being, including the feeling of hope/hopelessness (Echezarraga et al, 2022). Consistently, the hope and resilience scores have shown a positive correlation between each other, as converging factors in the framework of recovery and well-being (Duggal et al, 2016;Nash, 2022). Interestingly, resilience was lower when patients reported higher psychopathology, depressive and anxiety symptoms as well as higher suicidality: this may confirm that resilience is diminished where severity of illness is higher leading to higher levels of vulnerability and poor coping strategies (Duggal et al, 2016;Favale et al, 2020;Nash, 2022).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This may reflect the evidence that resilience moderates the relationship between severity of depressive episodes in bipolar disorder and subjective well-being, including the feeling of hope/hopelessness (Echezarraga et al, 2022). Consistently, the hope and resilience scores have shown a positive correlation between each other, as converging factors in the framework of recovery and well-being (Duggal et al, 2016;Nash, 2022). Interestingly, resilience was lower when patients reported higher psychopathology, depressive and anxiety symptoms as well as higher suicidality: this may confirm that resilience is diminished where severity of illness is higher leading to higher levels of vulnerability and poor coping strategies (Duggal et al, 2016;Favale et al, 2020;Nash, 2022).…”
Section: Discussionmentioning
confidence: 73%
“…Kaleta and Mróz (2020) reported that hope has a direct impact on depressive symptoms among 77 patients psychotherapy patients but also that forgiveness may have a mediating role among the two factors. Thus, a ‘Hopeful Resilience’ is recommended in the context of psychosocial interventions for patients affected by mood and neurosurgical disorders in general (Duggal et al, 2016; Nash, 2022). Previously, Favale et al (2020) explored the relationship between hope, resilience and depressive symptoms, including suicidal ideation among patients affected by a current major depressive episode: they found an inverse correlation between higher levels of hope and resilience (as assessed with specific ratings) and lower severity of depression as well as and higher levels of resilience were associated with lower level of suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the constructs we choose in the current study (cognitive ability, depressive symptoms and psychological resilience) can be differentiated into different categories. For example, cognitive ability can be grouped into distinct cognitive components (such as attention, memory, and executive function) 49 or non-inclusive categories (such as rational evaluation or irrational rumination of information) 50 ; depressive symptoms can be caused by different situations, such as those related to failing to achieve someone else's goals or failing to achieve one's own de ned goals 3 ; resilience can either be hopeful or not 51 . Whether psychological resilience holds promise depends on how individuals interpret the threats they encounter.…”
Section: Discussionmentioning
confidence: 99%
“…The facilitator poses each of the prompts on the private Facebook group set up for the interaction between the participant and facilitator. Why the private Facebook group was chosen over other online platforms has been noted elsewhere in relation to the previous HeNReG [16,[74][75][76][77]. These reasons were further reinforced once the group became a one-on-one process.…”
Section: The Promptsmentioning
confidence: 99%
“…Nevertheless, the mechanisms underlying the formation and management of the memory traces are still poorly understood [13]. At the same time, it has been recognized that improving the mental health of individuals is effectively (though not easily) accomplished through focusing on enhancing personal narrative development [14][15][16][17]. As such, the second aim is to present a narrative research process founded and offered by the author specifically intended for health researchers experiencing burnout as an example of a method that has been found useful in enhancing personal narrative development in its demonstrated success regarding positive mental health outcomes in well-defined conditions.…”
Section: Introductionmentioning
confidence: 99%